Does Commodity Prices Drive Bitcoin Price? - Koapaha, Hartiny Pop (Program Pascasarjana STIE Amkop Makassar, 2023)
This study investigates the relationship between Bitcoin prices and commodity prices, including oil, gold, silver, and copper, using a neural network approach. On a sample of 2,805 observations, 1,952 (69.6%) were used for training, 853 (30.4%) for testing, and the entire sample was used for validation. Neural networks are ideally adapted for this type of analysis due to their ability to model non-linear relationships between variables and to process large datasets. The results of the analysis indicate that the relative relevance of each commodity in predicting Bitcoin prices varies. Copper was determined to be the most significant commodity, followed by oil, silver, and gold. These results may be beneficial to investors, policymakers, and academics as they shed light on the interrelationships between Bitcoin and commodity markets. The findings of the study suggest that fluctuations in copper prices have a greater impact on Bitcoin prices than other commodities. Copper is utilized in numerous industries, including construction, electronics, and transportation. The results also indicate that shifts in the prices of oil, silver, and gold have a significant, albeit lesser, effect on Bitcoin prices. This study contributes to the comprehension of the relationship between Bitcoin and commodity prices, providing investors and policymakers with valuable insights. Keywords: bitcoin, copper, gold, oil, commodities price, silver